A Rare Complication of Vasovagal Syncope Induced by Pulsed Radiofrequency in a Patient with Cervical Spondylosis and Occipital Neuralgia: A Case Report - Fajar Ristranda; Buyung Hartiyo Laksono; Taufiq Agus Siswagama (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Pulsed radiofrequency is widely utilized as a minimally invasive neuromodulation technique for managing chronic neuropathic pain, including cervical radicular pain and occipital neuralgia. While pulsed radiofrequency is generally celebrated for its robust safety profile and absence of thermal tissue destruction, unexpected autonomic complications remain poorly characterized in the literature. Case presentation: A 41-year-old female with a six-month history of chronic cervical root syndrome (C3-C6) and refractory occipital neuralgia presented for interventional pain management. Following a comprehensive clinical and radiological evaluation, the patient underwent fluoroscopy-guided pulsed radiofrequency of the bilateral C3 and C4 dorsal root ganglia and the greater and lesser occipital nerves. The procedure was technically successful and uneventful. However, approximately 24 hours post-procedure, the patient experienced a sudden, profound episode of vasovagal syncope, characterized by acute hypotension, bradycardia, and a precipitous drop in consciousness (Glasgow Coma Scale: E3V3M6). Immediate resuscitation, including intravenous fluid boluses and continuous hemodynamic monitoring, led to a full neurological recovery. At follow-up, the patient reported significant attenuation of both radicular and occipital pain scores. Conclusion: This report documents a rare and severe episode of delayed vasovagal syncope following upper cervical and occipital pulsed radiofrequency neuromodulation. The temporal association suggests a complex neuro-autonomic reflex, potentially mediated by the trigeminocervical complex and sudden withdrawal of chronic sympathetic tone. Clinicians performing cervical pulsed radiofrequency must remain vigilant regarding delayed autonomic dysregulation, necessitating extended postoperative observation protocols in susceptible individuals.